An Empirical Analysis of Banking Reform Indicators and Financial Sustainability in The Iraqi Economy (2010–2023)‎ - Hadeed, Nabaa Hussein; Al‐Hussaini, Dr. Ahmed Khalil (International Journal of Accounting and Economics Studies, 2025)
This study aims to measure and analyze the impact of banking reform indicators—assets, deposits, credit, capital adequacy, and liquidity—on financial sustainability in the Iraqi economy from 2010 to 2023. Using a descriptive and quantitative approach based on Central Bank ‎reports, the study examines how these indicators influence fiscal stability through regression analysis. Results show that bank credit has a ‎statistically significant and positive impact on financial sustainability indicators, particularly the domestic debt-to-GDP ratio, while other ‎reform indicators exhibit limited effects. The findings highlight the essential role of the banking sector in supporting fiscal balance and ‎reducing reliance on oil revenues. The study recommends strengthening credit policy, expanding sustainable financing, and enhancing cooperation between the public and private sectors to achieve long-term financial sustainability.
Keywords: Banking Reform; Financial Sustainability; Bank Credit; Liquidity; Iraq